Relation between plasma lipids and relapse of idiopathic nephrotic syndrome in children (BIRDEM Medical Journal, 2020)
Background: Nephrotic syndrome (NS) is one of the most common renal diseases in children. It is a chronicchildhood disorder with a course of relapse and remission. Hyperlipidemia is a constant feature (95% cases)of minimal change nephrotic syndrome (MCNS) having serum cholesterol >250 mg/dl. Both increased synthesisand decreased clearance of lipoproteins may contribute to the hyperlipoproteinemia which frequently complicatesthe NS. Persistent hyperlipidemia can lead to relapse of NS which is a potential risk factor for progression ofglomerular injury. Persistent hyperlipidemia and frequent relapse of NS are further responsible forcardiovascular disease and progressive glomerular damage leading to renal failure. This study was done todetermine relationship between plasma lipids and relapse of idiopathic NS in children.Methods: This prospective study was carried out from July 2015 to June 2017 at the Department of Paediatricsin Sylhet MAG Osmani Medical College Hospital. Patients with the diagnosis of NS fulfilling the inclusioncriteria were included in this study purposively. A total of 50 children were included into this study. Theprimary end point was to determine plasma lipids level in children having idiopathic NS at acute phase, inremission and at 6 months after completion of treatment. The secondary end point was to evaluate the relationshipbetween persistent hyperlipidemia in remission phase and relapse of NS.Results: Among 50 children with clinical diagnosis of NS, 35 were first episode and 15 were in relapse cases.Among the first episode NS cases serum lipids level were decreased significantly during remission but HDLwas increased, whereas in relapse cases even during remission serum lipids level were significantly higher.After six months of follow up, out of 50 patients 28 patients had persistent remission and 22 patients hadrelapsed. The relationship between plasma lipids level and the incidence of relapse showed that acute lipidfraction levels were not risk factor in relapsing NS. Only the triglyceride level during remission was a riskfactor in relapsing NS (p